KAJIAN PENGGUNAAN MATEMATIKA DALAM BIDANG PERIKANAN - AMINULLAH AMINULLAH; SITI SOLIHUN; NI KADEK PUJI ASTUTI (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this research is to examine the use of mathematics in the field of fisheries. This literature review research examines scientific articles or research journals consisting of 7 national journals and 5 international journals. The study is limited to taking the results of previous research which includes results related to the use of mathematics in the field of fisheries. The results of the study show that mathematics in the field of fisheries is proven to be widely used, both in the use of mathematics on basic matters or entrenched habits (ethnomathematics) such as counting the number of fish, calculating feed, calculating the area of ponds, calculating buying and selling, weighing seeds and feed and predicting schedules. harvest and others. The use of more specific mathematics, for example ethnomathematics in the cultivation process by Indramayu shrimp cultivators, application of mathematical modeling to determine the growth in weight of a fish species, construction and dynamic analysis of mathematical models of fishing systems (a case study of the Nusantara Brondong fishing port), mathematics as a tool for efficient fisheries management and economic growth in Gashua, application of optimum control on fish harvesting models in non-reserved zones taking into account reserve zones, mathematical modeling applied to renewable fisheries management, mathematical modeling of predator-prey fisheries in polluted water ecosystems, mathematical modeling applied to sustainable management of marine resources, marine capture fisheries production, rainfall, and sea surface temperature with vector autoregressive (VAR) models, mathematical models of fish harvesting with selective harvest policies, and least square method mathematical models (least square method) on body shape fishing boat